Relationship Between Family Knowledge Levels and Dengue Fever (DF) Prevention Practices in the Working Area Work Area of the Pahandut Public Health Center Palangka Raya - Ripka Kristin; Mariaty A. Sangkai; Anggreni Ade Putri (PROMOTOR, 2026)
Background: Dengue fever is a disease transmitted by the bite of a mosquito called Aedes aegypti. This disease remains a public health issue in Indonesia, and its rate of spread in Indonesia is among the highest in Southeast Asia. DHF can be prevented by implementing the 5M method, such as draining water reservoirs, covering water containers, recycling and utilizing used items, spreading abate powder, and planting mosquito repellent plants. Objective: To determine the relationship between the level of family knowledge and DHF prevention practices in the working area of the Pahandut Community Health Center in Palangka Raya City. Research Method: Quantitative, using a cross-sectional approach. The sample in this study consisted of 99 respondents, using accidental sampling technique. Data analysis was performed using univariate and bivariate analysis with the chi-square test. Results: Significant results were obtained with a p-value of 0.002 < 0.05, which means that there is a significant relationship between the level of family knowledge and dengue fever prevention practices at the Pahandut Community Health Center in Palangka Raya City. Conclusion: The results of this study indicate that there is a significant relationship between the level of family knowledge and the practice of preventing dengue fever (DF) at the Pahandut Community Health Center in Palangka Raya City. It is hoped that health centers can increase efforts to prevent and control DBD through health education about DBD, starting from how it is transmitted, its symptoms, prevention practices, and the importance of seeking immediate medical attention when symptoms appear.